2014
DOI: 10.1002/spe.2268
|View full text |Cite
|
Sign up to set email alerts
|

A tool to improve code‐first Web services discoverability through text mining techniques

Abstract: SummaryService‐oriented development is challenging mainly because Web service developers tend to disregard the importance of the exposed service APIs, which are specified using Web Service Description Language (WSDL) documents. Methodologically, WSDL documents can be either manually generated or inferred from service implementations using WSDL generation tools. The latter option, called code first, is the most used approach in the industry. However, it is known that there are some bad practices in service impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 48 publications
(113 reference statements)
1
34
0
Order By: Relevance
“…However, services used by the clients are also embedded using classes and methods; thus, there is a need to study the evolution of smells in OO and SO. Moreover, SO systems can be implemented by using various technologies, and there are different tools, eg, Java2WSDL, used to generate a representation of services from OO code . SOAP services can be implemented using the code‐first or contract‐first approach, and OO source code metrics can be reused to detect antipatterns for the code‐first approach.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, services used by the clients are also embedded using classes and methods; thus, there is a need to study the evolution of smells in OO and SO. Moreover, SO systems can be implemented by using various technologies, and there are different tools, eg, Java2WSDL, used to generate a representation of services from OO code . SOAP services can be implemented using the code‐first or contract‐first approach, and OO source code metrics can be reused to detect antipatterns for the code‐first approach.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies reported antipatterns and code smells in different types of services, eg, antipatterns in SOAP services and WSDL (Web Service Description Language) interfaces, in REST, and in SCA (Service Component Architecture) . The data sets used in these studies for their experimental validations relied on OO code.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we pointed out in Section 3.1, domain-specific ontologies are difficult to specify in order to be truly useful [12]. This is the case with the experiment in the extended ontology-based approach [38].…”
Section: Discussionmentioning
confidence: 99%
“…[11]. However, domain-specific ontologies are often avoided in real life applications because they are difficult to specify [12]. Thereby, the lack of complete and relevant domain-specific ontologies hinders the applicability of ontology-based approaches in practice [13,14].…”
Section: Introductionmentioning
confidence: 99%